Mercury concentrations in tuna blood and muscle mirror seawater methylmercury in the Western and Central Pacific Ocean. (July 2022) - Barbosa, Romina V.; Point, David; Médieu, Anaïs; Allain, Valérie; Gillikin, David P.; Couturier, Lydie I.E.; Munaron, Jean-Marie; Roupsard, François; Lorrain, Anne
Abstract: Understanding the relationship between mercury in seafood and the distribution of oceanic methylmercury is key to understand human mercury exposure. Here, we determined mercury concentrations in muscle and blood of bigeye and yellowfin tunas from the Western and Central Pacific. Results showed similar latitudinal patterns in tuna blood and muscle, indicating that both tissues are good candidates for mercury monitoring. Complementary tuna species analyses indicated species- and tissue- specific mercury patterns, highlighting differences in physiologic processes of mercury uptake and accumulation associated with tuna vertical habitat. Tuna mercury content was correlated to ambient seawater methylmercury concentrations, with blood being enriched at a higher rate than muscle with increasing habitat depth. The consideration of a significant uptake of dissolved methylmercury from seawater in tuna, in addition to assimilation from food, might be interesting to test in models to represent the spatiotemporal evolutions of mercury in tuna under different mercury emission scenarios. Highlights: Spatial trends of Total [Hg] (THg) concentrations in tuna muscle and blood are identical. Blood to muscle Hg ratio increases with depth habitat of tuna species. Opposed to other tuna, THg was higher in blood compared to muscle in bigeye. THg in blood and muscle mirror seawater methylmercury concentration profiles. Direct uptake of methylmercury by tuna might be more important than currently thought.